The production, use and importance of flint tools in the archaic period and the old kingdom of Egypt - Kobusiewicz, Michał (Archaeopress archaeology., 2015)
This volume represents a selection of contributions on Mediterranean themes from a wider international interdisciplinary conference on Magical Texts in Ancient Civilizations, organised by the Centre for Comparative Studies of Civilizations at Jagiellonian University in Krakow.